Chapter La famiglia di Giovanni Boccaccio nelle pergamene olivetane - Regnicoli, Laura (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2021)
The essay focuses on a documentary corpus that belonged to the San Miniato archive: the papers of Banco di Francesco Botticini, which came to the monastery at the beginning of the 15th century. Botticini's legacy can be reconstructed in about fifty parchments (represented here in an Appendix as register or excerpt), and offers interesting evidence on the Boccaccio's family, linked to Banco Botticini by neighborhood relations and common acquaintances. Eleven 'Olivetan parchments' bear references to Boccaccio and are able to show different but still close relationships: from the sincere ones with messer Giovanni to the stormy with his brother, Iacopo, up to the long-lasting bond with the Iacopo's sons, heirs of Boccaccio, who remained in the legal guardianship of Banco Botticini for many years.